Can China's New Rural Cooperative Medical System Improve Farmers' Subjective Well-Being? - Qi, Wenhao; Liu, Fang; Zhang, Tian; Qi, Xiulin (Frontiers in Public Health, 2022)
The New Rural Cooperative Medical System (NRCMS) is one of the essential systems for ensuring public health in rural China. This paper investigates the effect of farmers' participation in the NRCMS on their subjective well-being and its mechanisms using data from the Chinese General Social Survey 2017. The results show that farmers' participation in the NRCMS significantly enhances their subjective well-being, and these results remain robust after regression with the instrumental variables method and propensity score matching method. Further analysis of the mechanisms suggests that participation in the NRCMS can enhance farmers' subjective well-being by increasing their consumption levels other than medical consumption. Moreover, medical consumption levels play a negative role in participating in the NRCMS on farmers' subjective well-being, which can be explained as the “masking effect.” The regression results of the subsamples show that the higher a farmer's income is, the less his or her participation in the NRCMS enhances subjective well-being. And the effect of participation in the NRCMS on farmers' subjective well-being is not significant if their health status is too high or too low.